2021
DOI: 10.1155/2021/6635936
|View full text |Cite
|
Sign up to set email alerts
|

Long Noncoding RNA RP11-357H14.17 Plays an Oncogene Role in Gastric Cancer by Activating ATF2 Signaling and Enhancing Treg Cells

Abstract: Background. Gastric cancer (GC) is one of the most common malignant tumors in the world. The potential functions and mechanisms of long noncoding RNAs (lncRNAs) in GC development are still unclear. It is of great significance to explore the prognostic value of LncRNA signatures for GC. Methods. LncRNAs differently expressed in GC and their prognostic value were studied based on The Cancer Genome Atlas (TCGA) database. The functional regulatory network and immune infiltration of RP11-357H14.17 were further stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Generally, in response to many forms of cellular stress, especially oxidative stress, ATF2 is phosphorylated by multiple upstream kinases, translocates to the nucleus and increases transcriptional activity [ 16 ]. Although the oncogenic role of ATF2 in GC has been reported in several studies [ [17] , [18] , [19] ], there is still a lack of experimental evidence in vitro and in vivo, especially its relationship with clinicopathological parameters and prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, in response to many forms of cellular stress, especially oxidative stress, ATF2 is phosphorylated by multiple upstream kinases, translocates to the nucleus and increases transcriptional activity [ 16 ]. Although the oncogenic role of ATF2 in GC has been reported in several studies [ [17] , [18] , [19] ], there is still a lack of experimental evidence in vitro and in vivo, especially its relationship with clinicopathological parameters and prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, ATF2 is often aberrantly activated in GC. For example, lncRNA RP11-357H14.17 acts as a cancer-promoting factor in GC by activating ATF2 signaling pathway (Xiaoli et al, 2021). Nuclear ATF2 binds to the miR-132 promoter region to upregulate miR-132, and miR-132 targetedly regulates the CD44/FN1/Sirt1/BDNF signaling pathway and recruits lymphocytes to attack GC cells to suppress hematogenous metastasis (Liu et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…ATF2 activation is mainly achieved via phosphorylation modification after stress stimulation (Watson et al, 2017). Phosphorylated ATF2 binds with specific sequences in target genes’ promoter regions, such as cell cycle molecules, adhesion molecules, and apoptosis‐associated molecules, thus activating the expression of target genes and ultimately participating in modulating various biological processes of cells (Bhoumik et al, 2002; Liu, Li, et al, 2020; Xiaoli et al, 2021). For instance, ATF2 can bind to the promoter of NEAT1 to promote its transcription, thereby downregulating miR‐26a‐5p and ultimately promoting lung cancer progression (Liu, Li, et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The dysregulation of these lncRNAs can lead to the occurrence and progression of tumors. 20,21 In the bioinformatics analysis, we identified a GC-associated lncRNA, LINC01088, reduced expression in GC tissues and cell lines. Our analysis of clinical revealed that LINC01088 expression was lower in GC tissue and cell lines, which matched the bioinformatics findings.…”
Section: Discussionmentioning
confidence: 99%